Cell-mediated immune responses to different formulations of a live-attenuated tetravalent dengue vaccine candidate in subjects living in dengue endemic and non-endemic regions. Issue 9 (2nd September 2019) - Moris, Philippe; Bauer, Kristen M.; Currier, Jeffrey R.; Friberg, Heather; Eckels, Kenneth H.; Esquilin, Ines O.; Gibbons, Robert V.; Innis, Bruce L.; Jarman, Richard G.; Simasathien, Sriluck; Sun, Peifang; Thomas, Stephen J.; et al.
ABSTRACT: Three phase II randomized trials evaluated the safety/immunogenicity of two formulations of live-attenuated tetravalent dengue virus (TDEN) vaccine in dengue-endemic (Puerto Rico, Thailand) and non-endemic (US) regions (NCT00350337/NCT00370682/NCT00468858). We describe cell-mediated immune (CMI) responses; safety and humoral responses were reported previously. Participants received two doses of vaccine or control (placebo or the precursor live-attenuated TDEN vaccine) 6 months apart. Selected US participants received a booster 5–12 months post-dose 2. Evaluated subsets of the per-protocol cohorts included 75 primarily dengue virus (DENV)-unprimed US adults, 69 primarily flavivirus-primed Thai adults, and 100 DENV-primed or DENV-unprimed Puerto Rican adults/adolescents/children. T-cell responses were quantified using intracellular cytokine staining (ICS; DENV-infected cell-lysate or DENV-1/DENV-2 peptide-pool stimulation) or IFN-γ ELISPOT (DENV-2 peptide-pool stimulation). Memory B-cell responses were quantified using B-cell ELISPOT. Across populations and age strata, DENV serotype-specific CD4 + T-cell responses were slightly to moderately increased (medians ≤0.18% [ICS]), DENV-2–biased, and variable for both formulations. Responses in unprimed subjects were primarily detected post-dose 1. Response magnitudes in primed subjects were similar between doses. Multifunctional CD8 + T-cell responses were detected after peptide-pool stimulation. T-cell responses were mostly directed to DENV nonstructural proteins 3 and 5. Memory B-cell responses were tetravalent, of low-to-moderate magnitudes (medians ≤0.25%), and mainly observed post-dose 2 in unprimed subjects and post-dose 1 in primed subjects. A third dose did not boost CMI responses. In conclusion, both formulations of the live-attenuated TDEN vaccine candidate were poorly to moderately immunogenic with respect to B-cell and T-cell responses, irrespective of the priming status of the participants. Abbreviation: ATP: according-to-protocol; ICS: Intracellular Cytokine Staining; NS3: Nonstructural protein 3; ELISPOT: Enzyme-Linked ImmunoSpot; JEV: Japanese encephalitis virus; PBMC: peripheral blood mononuclear cells